(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The research examined the need for innovative focus of teaching activities on the example of students in higher education. During the study identify the possibility of using the specific innovative teaching methods in the preparation of students of economic specialties. Established that the presence of exclusively traditional educational approaches has led to a mismatch of learning outcomes and knowledge practitioner graduates meet the needs of individual enterprises. Determined the significance of innovative teaching methods in the educational process, the problematic issues that arise in connection with the transformation processes in the formation of existing innovative technologies in education and the possibility of their use in the preparation of students of economic specialties.